Model Implementasi Kurikulum dalam Pembelajaran dan Implikasinya terhadap Kepesertadidikan - Sukardi Ismail; Lamsike Pateda (Jurnal Ilmiah AL-Jauhari: Jurnal Studi Islam dan Interdisipliner, 2023)
The article aims to analyse the curriculum implementation model in learning and its implications for education. The method used is skinataif. The results of the study show that the curriculum has an important role in improving the quality of education and strengthening learners' education. Appropriate implementation of the curriculum according to students' needs can help improve students' skills and knowledge, increase learning motivation, strengthen students' participation and involvement in the learning process, develop important life skills, increase accountability in education and improve students' future opportunities. A good and appropriate curriculum implementation model needs to be developed and implemented consistently to strengthen student participation and improve the overall quality of education. So that learners can be ready to face future challenges and competition and become successful and contributing members of society